Defect detection of rolling element bearings rotor system using vibration measurements of bearings base - Hammza, Tariq M.; Mohammed, Jamal A. K.; Ayed, Sahar A. (AIP conference proceedings, 2024)
The first step in lowering unwanted vibration, cutting maintenance costs, and raising machine uptime is understanding and applying the foundations of rotational parameters. To prevent resulting damages, it is essential to spot undesirable situations while performing the procedure. To improve availability and dependability, early identification is crucial. The most often utilized mechanical components in rotating machinery that is subject to heavy loads and fast rotational speeds are REBs. The surface of another element comes into touch with the flaw in a rolling element, generating an impact force that causes the bearing to respond impulsively. The ball, inner race, outer race, and train cage of the bearing are all affected if there is a flaw in one element of the REB. The flaw in the rolling parts could have major catastrophic effects and result in expensive downtime. The vibration analysis approach, which is a trustworthy and accurate way to find defects in the bearing elements, is employed for this purpose. One bearing element represents the bearing's normal condition for four distinct operating speeds in the vibration data that was recorded and utilized for determination and validation (0, 1000, 2000, 2500 rpm) and the other is defective. By analyzing and processing the obtained data with LabVIEW, the dynamic characteristics of the system of rotating machinery, the axis trajectory, and spectrum parameters may be determined. The findings acquired from the experiments have provided illustrations and explanations.